Influence of acid and low-temperature adaptation on pulsed electric fields resistance of Enterococcus faecium in media of different pH. (February 2018) - Fernández, Ana; Cebrián, Guillermo; Álvarez-Ordóñez, Avelino; Prieto, Miguel; Bernardo, Ana; López, Mercedes
Abstract: This investigation was undertaken to study the inactivation of Enterococcus faecium ATCC 49624 by pulsed electric fields (PEF) treatments after exposure to sublethal acid and cold stresses. Cells were grown in Brain Heart Infusion (BHI) buffered to pH 7.4 (non-acid-adapted cells) and BHI acidified to pH 5.4 with acetic, ascorbic, citric, lactic, malic and hydrochloric acids (acid-adapted cells). Fresh and refrigerated cultures (kept at 4 °C for up to 1 month) were treated by PEF at 37 kV/cm in citrate-phosphate buffer of different pH (4.0, 5.5 and 7.0), at specific energies ranging from 79 to 1580 kJ/kg. Results demonstrated that acid adaptation exerted a different effect on the PEF resistance of E . faecium depending on the pH of the treatment medium. Thus, when treated in a medium of pH 7.0, previous acid adaptation, regardless of the type of acidulant used, reduced the calculated δ values (specific energies required to inactivate the first log10 cycle of the population) by approximately two-fold. By contrast, in a medium of pH 4.0, acid-adapted cells showed a higher PEF resistance than non-adapted cells. On the other hand, exposure to 4 °C reduced the PEF resistance of acid-adapted cells, but not that of non-acid-adapted cells. Results obtained in this study suggested that, after the same PEF treatments, the number of electroporated cells was lower for non-acid-adapted cells, but that acid-adapted cells displayed a superior ability to repair sublethal damages caused by PEF. Nevertheless, exposure to refrigeration conditions would significantly reduce this damage repair ability. Finally, FT-IR spectroscopy measurements indicated that growth of E . faecium cells under acid conditions caused an increase in membrane fluidity. It was also observed that refrigerated storage resulted in a significant ( p  < 0.05) reduction in membrane fluidity for acid-adapted cells but not for non-acid-adapted cells, with a potential impact on PEF resistance. Industrial relevance: Given the inability of PEF to inactivate spores, pasteurization of acid products such as fruit juices appears as one of the more feasible applications for this technology. Microbial cells present in these products would have, very likely, undergone a process of adaptation to this acid pH; however, the impact of this phenomenon on microbial PEF resistance has only been scarcely investigated. Thus, the objective of this work was to study the inactivation of Enterococcus faecium by PEF treatments after sequential exposure to sublethal acid and cold stresses. This work will provide very valuable data for process design to further develop PEF application and improve understanding of microbial inactivation. Highlights: Acid adaptation increased E . faecium PEF resistance in acid media (pH 4.0) but not at neutral pH. Exposure to refrigeration temperatures (4 °C) reduced the PEF resistance of acid adapted cells. This sensitization could be due to a decreased capability to repair sublethal damages. Acid adapted E . faecium displayed higher membrane fluidity. Refrigerated storage led to reduced membrane fluidity for acid-adapted cells.